THE IMPORTANCE OF DIGITAL MEDICINE IN INCREASING THE PROFESSIONAL MOTIVATION OF DOCTORS - Bobur T. Khalmukhamedov (Central Asian Journal of Medicine, 2024)
Digital medicine is currently developing rapidly, showing its relevance in the field of education, as well as clinically, it is a new direction in the healthcare system of Uzbekistan. The purpose of the study: to study and analyze the interest of future family doctors in training in telemedicine technologies in the field of medicine, to determine the factors affecting the effectiveness of training and the attitude to the implementation of telemedicine consultations. Material and methods: analysis and generalization of scientific, methodological and foreign literature, test questionnaire for future family doctors and analysis of its results. Results. Prior to the test survey, students completed a 3-day course on the various information technologies used in healthcare today. Among the 30 students surveyed, 6 (17 %) answered correctly for the term telemedicine technology. A positive aspect of increasing students’ motivation for education was their desire to learn telemedicine and apply it in their work. The majority of students - future doctors (75 %) want to learn about telemedicine in the future, to improve their skills in legal issues, telemedicine technologies, the basics of the interaction of traditional and telemedicine technologies in diagnosis, treatment and rehabilitation. said. Conclusion. The introduction of telemedicine technologies into the educational process will serve to prepare doctors for effective work in hospitals and polyclinics in the future and provide high-quality medical care to patients. Telemedicine is a very important area in medical education and it is important to include such education in the curricula.